PELESTARIAN BAHAN PUSTAKA DI RUANG DEPOSIT DINAS PERPUSTAKAAN DAN KEARSIPAN KALIMANTAN BARAT - Sari, Dewi Maulidiyah; Madeten, Sisilya Saman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is based on the researcher's desire to know the preservation of library collections at Deposit room of  Library Collection in Library and Archivat Services West Kalimantan. The purpose of this final project is to know and explain about the cause of damage and an effeorts to faced the trouble when carrying out preservation library materials. At this research the effort preservation is restoration,for the preservation library materials damage is covering the book and fumigation.Another trouble that must be faced is limited room condition,budget and limited human resources. The researches used qualitative method with a descriptive from of research,Techniques data collection was used is observation,interviews and documentation with a peoples for informant.The research result show the preservation activity has been doing just cover the book,restoration and fumigation.The most trobled thing is the budget and limited human resources.Keywords :  Preservation, Conservation